THEORISING CASTE AND ADDRESSING EDUCATION: A COMPARATIVE STUDY OF AMBEDKAR AND GANDHI - Sharvender (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The caste system in India is a complex social structure that has persisted despite constitutional and legal reforms. Despite these efforts, it still leads to socio-economic disparities and discrimination. People often view education as a transformative tool to challenge these norms. This paper is analysing the theoretical foundation of caste and the educational philosophies of Dr. B.R. Ambedkar and Mahatma Gandhi, two prominent leaders in India, to understand their contributions to caste and social reform. Ambedkar condemned caste systems and emphasised education for the poor, whereas Gandhi linked education with rural India’s enlightenment. This analysis also aims to understand the historical and political context; the role of education in social mobility, social inequality, and marginalisation; education policies and strategies; and the educational philosophies of Ambedkar and Gandhi, offering practical recommendations for socially engaged individuals in their pursuit of social justice.